Tinjauan Yuridis Undang-Undang Informasi dan Transaksi Elektronik Terhadap Tindak Pidana Penipuan pada Toko Jujur Store di Denpasar: Studi Kasus Putusan Nomor 995/Pid.B/2023/PN Dps (International Forum of Researchers and Lecturers, 2026)
This research is motivated by the rise of online sales fraud cases on the island of Bali that are detrimental to consumers, the purpose of this research is to analyze it from the aspect of juridical studies and the basis of judges' decisions in deciding cases, this research uses a normative method with a library approach, the results of the study show that online fraud crimes utilize digital technology to manipulate data, here the defendant uses fake transfer evidence as a tool to deceive the store that meets the elements in Article 378 of the Criminal Code, namely the intention to benefit oneself unlawfully, and Article 35 of the ITE Law concerning manipulation of electronic information with the aim of making the data considered authentic, the basis for the judge's consideration to pass a verdict because the existence of photos of transfer evidence and the victim's account balance is sufficient to convince the judge that the defendant is guilty. Legal protection for victims of online fraud has been regulated in the Consumer Protection Law, the ITE Law and government regulations related to electronic transactions, but to strengthen preventive and systemic efforts, public education and increased capacity of law enforcement officers are needed, With the latest regulations such as Law No. 1 of 2024 concerning the second amendment to the ITE Law, Presidential Decree No. Law No. 49 of 2024 concerning the National Strategy for Consumer Protection and Minister of Trade Regulation No. 17 of 2024 concerning the National Action Plan for Consumer Protection have implications for strengthening legal protection for victims of online fraud, which is expected to provide a sense of security in digital transactions.